2014
DOI: 10.1002/ptr.5147
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Safety Evaluation and Biochemical Efficacy of a Carum carvi Extract: Results from a Randomized, Triple‐Blind, and Placebo‐Controlled Clinical Trial

Abstract: Carum carvi L. (Apiaceae) is known as caraway, and its derivatives find wide medicinal use for health purposes, including for gastrointestinal problems and obesity. Since there is inconsistency among the reports on the safety of this plant in humans, this research was aimed at assessing the safety of a characterized caraway aqueous extract (CAE) in a randomized, triple-blind, placebo-controlled study. Seventy, overweight and obese, healthy women were randomly assigned into placebo (n = 35) and plant extract (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Anti-inflammatory, spasmolytic, antimicrobial, antioxidant, carminative and immunomodulatory properties of caraway along with anticolitis (Keshavarz et al 2013). Daily intake of caraway extract for gastrointestinal problems in obese subjects for 12 weeks has not adverse effects (Kazemipoor et al 2014) with antiobesity effects in women (Kazemipoor et al 2013); cholesterol and triglycerides lowering activities in normal and STZ diabetic rats (Lemhadri et al 2006) were reported.…”
Section: Introductionmentioning
confidence: 99%
“…Anti-inflammatory, spasmolytic, antimicrobial, antioxidant, carminative and immunomodulatory properties of caraway along with anticolitis (Keshavarz et al 2013). Daily intake of caraway extract for gastrointestinal problems in obese subjects for 12 weeks has not adverse effects (Kazemipoor et al 2014) with antiobesity effects in women (Kazemipoor et al 2013); cholesterol and triglycerides lowering activities in normal and STZ diabetic rats (Lemhadri et al 2006) were reported.…”
Section: Introductionmentioning
confidence: 99%
“…1). These bioactive compounds present in CAE may be effective, individually or synergistically, in the management of obesity, reducing body size, body weight, body fat, and appetite (Kazemipoor et al, 2014b).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, body muscle percentage showed a significant increase in the CAE group compared with the placebo group. Safety studies on this plant-based composition, including blood biomarkers, kidney function, liver function, heart function, systolic and diastolic blood pressure, lipid profile, complete blood count test, and urine test, showed no significant side effects on participants during the treatment period (Kazemipoor et al, 2014b). Furthermore, the phytochemical content of CAE was analyzed by gas chromatography-mass spectrometry (GC-MS) showing that the predominant ingredients detected from the GC-MS analysis were a range of different volatile and phenolic compounds (Kazemipoor et al, 2013).…”
Section: Introductionmentioning
confidence: 95%
“…for new biological responses. One recent study found that an aqueous extract of caraway seed could have an obesity-reducing effect [102,103]. Finally, microfluidic, lab-on-achip approaches to the chemical and biological assessment of plant samples in the field (previously referred to as "pharmacognosy in a suitcase") [25-27, 29, 30, 34] would save significantly on the drying, transportation, and macro-analytic processes required to evaluate the optimal time for accessing plant materials for therapeutic purposes based on the levels of their bioactive agents.…”
Section: Abcs Of Ecopharmacognosymentioning
confidence: 99%